1-Hydroxy-3-(3-methylbut-2-enyloxy)xanthone - Luis Gales; Raquel A. P. Castanheiro; Madalena M. M. Pinto; Ana M. Damas (Acta Crystallographica Section E, 2009)
In the title compound, C18H16O4, a monoprenylated xanthone, the xanthone skeleton exhibits an essentially planar conformation (r.m.s. deviation 0.0072 Å) and the isoprenyl side chain remains approximately in the mean plane of the xanthone unit, making a dihedral angle of 4.5 (2)°. The hydroxyl group forms an intramolecular O—H...O hydrogen bond. Moreover, there is a weak intermolecular C—H...O interaction between a ring C atom and the xanthene O atom. In the crystal structure, there are no intermolecular hydrogen bonds and the crystallographic packing is governed by van der Waals forces, leading to an arrangement in which the molecules assemble with their planes parallel to each other, having a separation of 3.6 (3) Å.